The reproduction/challenging of tribal prejudice between Shonas and Ndebeles through jokes and cartoons that are circulated on Whatsapp. - Ndlebe, Perpetual (Midlands State University, 2017)
This study explores how the jokes and cartoons that are circulated on WhatsApp fuel/challenge ethnic prejudices between the Shonas and Ndebeles. Ethnic differences and tensions which escalate into conflict between Shona and Ndebele ethinic groups date back to the pre-colonial period. Social media networks particularly WhatsApp seem to have presented the two groups with an opportunity to entrench or question these negative attitudes between them. To assess the way new social networking sites complicates ethnic relations between Shonas and Ndebeles, data was gathered through in-depth interviews with MSU students both Ndebeles and Shonas and from experts on ethnicity. Focus group discussions were also held with MSU students purposively selected on the basis of their ethnic affiliation as either Shonas or Ndebeles. The study found out that the jokes and cartoons that are circulated on WhatsApp seem to entrench ethnic prejudice between the Ndebeles and the Shonas. On the other hand, though to a lesser extent, cartooning and jokes on social media are also read and consumed as a way of laughing at and lampooning such attitudes towards the other. The study makes recommendations particularly to government and relevant policy makers on how they can exploit social media platforms to foster greater amity between different ethnic groups that make up the Zimbabwean nation.